Studying some Immunological and Hormonal profiles in Infertile Male - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
The present study was designed to evaluate the immunological status in a sample of Iraqi males with primary infertility and them age range18-55 years, who were attending the Centre of Infertility and in vitro Fertilization (Kamal Al-Samaraie Hospital, Baghdad) during the period December 2008 – April 2009. They were divided into three groups; 40 patients with anti-sperm antibodies (ASA), 20 patients with Asthenozoospermia (AST) and 20 patients with azoospermia (AZO). In adition to20 fertile males was as control group. The parameters of evaluations were standard seminal fluid analysis, anti-sperm antibodies and anti-mitochondrial antibodies in serum, Therefore, two types of samples were collected from each subject; seminal fluid and blood. The following results were obtained: 1. There was a significant (P ? 0.05) decrease count of sperms in ASA (44.6 x 106 sperm/ml) and AST (46.9 x 106 sperm/ml) patients as compared to controls (63.2 x 106 sperm/ml) but the the result with in normal limit. 2. Serum anti-sperm antibodies were positive in 100.% of ASA patients, while in AZO patients, a much lower percentage was observed (25% for serum), and a much lower percentage was observed in controls (5% for serum but these influence were not clear). In contrast, none of the AST patients were positive ASA. These results were positively correlated with the corresponding serum and seminal fluid level, and the highest level was observed in ASA patients (107.6 U/ml). These differences were statistically significant. 3. Serum AMA showed different percentages in ASA, AST and AZO patients and controls (37.5, 25.0 and 20.0, 15.0%, respectively), but these differences were not significant. However, their serum level was significantly increased in ASA patients as compared to controls (11.9 vs. 6.5 U/ml).